Urgency of the Harmonization of Interception Regulation in the Context of Law Enforcement - Fadhil, Moh. (Susbtantive Justice International Journal of Law, 2020)
Systems regarding the legal remedy of communication interception can be found in several regulations. However, those systems are not supported by horizontal harmonization since each regulation governs the mechanism differently, so there is a disparity among interception regulation. This paper analyzes the harmonization of wiretapping regulations in Indonesia from a law enforcement perspective with an inventory of regulations governing the current mechanism of interception. The results concluded that first, the disparity in intercepting authority of communication interception practice regulated by several institutions in the same form of crime eradication authority must be reformulated to restore overlapping regulations. Secondly, the interception regulation as a coercive force that derogates the right to privacy must contain detailed provisions in terms of a permit request and the wiretapping authority. The permit application must contain the purpose of the request for wiretapping permission descriptively. Moreover, these provisions must explicitly regulate legal subjects that are authorized to conduct wiretapping practice in the form of clear mechanisms and coordination with the direct superiors and court supervision regulating the interception procedure as well as the cooperation between law enforcement officials and telecommunications service providers. Third, prospectively interception regulations can be assessed from the political will of the legislators. The decision of the Constitutional Court No. 5/PUU-VIII/2010 mandates the need for horizontal harmonization of interception regulations in the form of the Interception Bill, which is also included in the 2019 National Legislation Program.